2017
DOI: 10.1111/nmo.13199
|View full text |Cite
|
Sign up to set email alerts
|

Obesity increases the risk of small intestinal bacterial overgrowth (SIBO)

Abstract: While obesity was significantly associated with SIBO, our findings suggest that alterations in gut pH, SBTT, and decline in species richness do not account for the obesity-SIBO relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 39 publications
2
30
1
1
Order By: Relevance
“…Another association between obesity and FGID is the gut microbiota. Increased risk of small intestinal bacterial overgrowth (28) and different gut microbiota composition (29) in obesity has been reported which might contribute to gastrointestinal dysmotility, excessive fermentation, altered visceral perception and gut permeability with their metabolites leading to pain-predominant FGID (30,31). Finally, obesity and FGID share common psychological comorbidities, such as stress, depression, and anxiety, which can contribute to each other's development and aggravate each other (32,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Another association between obesity and FGID is the gut microbiota. Increased risk of small intestinal bacterial overgrowth (28) and different gut microbiota composition (29) in obesity has been reported which might contribute to gastrointestinal dysmotility, excessive fermentation, altered visceral perception and gut permeability with their metabolites leading to pain-predominant FGID (30,31). Finally, obesity and FGID share common psychological comorbidities, such as stress, depression, and anxiety, which can contribute to each other's development and aggravate each other (32,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…PPIs increase gastric pH, which disrupts the native GI  microecosystem 12. PPI use has been previously associated with a decrease in lower GI tract microbial diversity; however, the clinical relevance of these findings is unclear 57. A recent twin study comparing concordance of leanness or obesity found that obesity was associated with a significant reduction in overall GI tract bacterial diversity 58.…”
Section: Discussionmentioning
confidence: 99%
“…Another association between obesity and FGID is the gut microbiota. Increased risk of small intestinal bacterial overgrowth (28) and different gut microbiota composition (29) in obesity has been reported which might contribute to gastrointestinal dysmotility, excessive fermentation, altered visceral perception and gut permeability with their metabolites leading to painpredominant FGID (30,31). Finally, obesity and FGID share common psychological comorbidities, such as stress, depression, and anxiety, which can contribute to each other's development and aggravate each other (32,33,34).…”
Section: Discussionmentioning
confidence: 99%